From evidence to practice: Implementation of the Housing First program in Poland - Bokszczanin, Anna (2021)
Likewise in other EU countries, also in Poland a large number of people experience homelessness. In particular, the growing number of long-term homeless people with complex mental problems, for whom effective help is a challenge for stakeholders, i.e. politicians, professionals, scientists and ordinary citizens, is worrying. An innovative solution in this areas is the Housing First (HF) program designed for long-term homeless people with mental problems and/or addictions. The effectiveness of the HF model were shown, among others, by the results of the HOME-EU research project implemented under the Horizon 2020 program. The goal of our article is to present the current situation of homeless people and outline the existing help system. We also want to show what barriers and challenges are connected to the implementation of the HF program in Poland.